PENERAPAN MODEL DISCOVERY LEARNING BERBANTU MEDIA SPINDU (SPIN EDUKASI) UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK SISWA KELAS 4 SDN WONOTINGAL SEMARANG - Musyahadah Dienulhaqqi; Darsimah Darsimah; Veryliana Purnamasari (Universitas Negeri Medan, 2021)
Abstract: Application of the Discovery Learning Model Assisted by Spindu Media (Spin Education) to improve thematic Learning Outcomes at Students of the 4 class SDN Wonotingal Semarang. The background of the research is the students’ abilities in problem-solving, finding new understanding and, thinking in critical ways. This can be seen from the students’ activities when they do the online learning, for example, the students pay less attention to the explanation given by the teacher, only a few students ask questions or have opinions about the material being taught. The use of innovative learning models is still lacking, due to time and distance limitations in online learning. While the researcher identified student learning outcomes, specifically HOTS-oriented questions with quite long reading material, the students still have some difficulties in answering the question. This study aims to improve the learning outcomes of students of the 4D class by applying the ‘discovery learning’ model with the help of spindu media (spin education) theme 9 Kayanya Negeriku at SD Negeri Wonotingal Semarang. The Classroom action research consists of three cycles wherein a cycle there are two meetings. The data collections used in this research are tests and non-tests. The data analysis technique used is qualitative and quantitative, using the percentage formula to conclude. The results showed an increase in learning outcomes from good to very good category. The research result showed that there was an increase in learning outcomes from good to very good category. Completeness of student learning outcomes in the pre-cycle was 26.7%, in the first cycle of the first meeting it increased to 33.3%, in the first cycle of the second meeting it increased to 46.7%, in the second cycle of the first meeting it increased to 60%, in the second cycle the second meeting increased to 73.3%, in the third meeting the first meeting increased to 80%, and in the third meeting the second cycle increased to 86.7%. The application of the discovery learning model with the help of spindu media (spin education) can improve learning outcomes for the theme 9 Kayanya Negeriku at students of the 4D class of SD Negeri Wonotingal Semarang. Keywords: discovery learning, thematic, learning outcomes Abstrak: Penerapan Model Discovery Learning Berbantu Media Spindu (Spin Edukasi) untuk Meningkatkan Hasil Belajar Tematik Siswa Kelas 4 SDN Wonotingal Semarang. Latar belakang yang mendorong penelitian ini adalah kemampuan siswa dalam memecahkan masalah, menemukan pemahaman baru dan berpikir kritis dalam pembelajaran tematik masih kurang. Hal ini terlihat dari aktivitas siswa saat pembelajaran secara daring melalui google meet, misalnya siswa kurang memperhatikan penjelasan yang diberikan oleh guru, hanya sedikit siswa yang bertanya atau berpendapat tentang materi yang diajarkan. Penggunaan model pembelajaran yang inovatif masih kurang, karena adanya keterbatasan waktu dan jarak dalam pembelajaran daring. Saat peneliti mengidentifikasi hasil belajar siswa melalui google form, terlihat pada soal-soal yang berorientasi HOTS dengan teks bacaan yang cukup panjang, siswa masih kebingungan dalam menuliskan jawabannya. Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa kelas 4D dengan menerapkan model pembelajaran discovery learning berbantu media spindu (spin edukasi) tema 9 Kayanya Negeriku di SD Negeri Wonotingal Semarang. Penelitian tindakan kelas yang terdiri dari tiga siklus, di setiap siklusnya ada dua pertemuan. Subjek penelitian ini adalah 15 siswa di kelas 4D SD Negeri Wonotingal Semarang yang mengikuti pembelajaran daring melalui google meet. Pengumpulan data menggunakan tes dan nontes. Teknik analisis data yang digunakan adalah secara kualitatif dan kuantitatif, dengan rumus persentase kemudian ditarik kesimpulan. Hasil menunjukkan adanya peningkatan hasil belajar dari kategori baik menjadi sangat baik. Ketuntasan hasil belajar siswa pada pra siklus yaitu 26,7%, pada siklus I pertemuan I meningkat menjadi 33,3%, pada siklus I pertemuan II meningkat menjadi 46,7%, pada siklus II pertemuan I meningkat menjadi 60%, pada siklus II pertemuan II meningkat menjadi 73,3%, pada siklus III pertemuan I meningkat menjadi 80%, dan pada siklus III pertemuan II meningkat menjadi 86,7%. Penerapan model discovery learning berbantu media spindu (spin edukasi) dapat meningkatkan hasil belajar tema 9 kayanya negeriku pada siswa kelas 4D SD Negeri Wonotingal Semarang. Kata kunci: discovery learning, tematik, hasil belajar.